Doenças de caprinos na região central do Rio Grande do Sul - Rosa, Fábio Brum (2012)
A retrospective study of the goat necropsies performed over a period of 48 years (1964 to 2011) at the Laboratório de Patologia Veterinária (LPV), Universidade Federal de Santa Maria (UFSM), Rio Grande do Sul state, Brazil, was performed. A total of 114 reports of goat necropsies were analyzed. Ninety five necropsies (83.33%) had a conclusive diagnosis and 19 (19.66%) had inconclusive diagnosis. Out of the conclusive cases, infectious and parasitary diseases were the most prevalent, followed, in decreasing order of prevalence, by metabolic and nutritional diseases, poisonings and toxi-infections, and developmental diseases. Hemonchosis was the most prevalent cause of death in this study. Eimeriosis and listeriosis were also important causes of goat deaths. Among the metabolic and nutritional diseases, urolithiasis, osteoporosis, pregnancy toxemia, malnutrition, and white muscle disease were the most prevalent. Mostly the infectious and parasitary diseases and the metabolic and nutritional diseases occurred many times as outbreaks, causing even more important economic losses. Other conditions or lesions that did not fit any of the above groups of diseases affected about 10% of the necropsied goats. In parallel, a study of cases of osteoporosis in goats, diagnosed in the LPV-UFSM, was performed. The epidemiology, clinicopathological changes and possible pathogenetic mechanisms were determined and discussed. Five goats, females, mix breed, with six months to six years of age, that were kept on natural pasture, without supplemental feed, and under overcrowding condition, were affected. The main clinical signs were weight loss, limited mobility, and recumbence for long periods. The main gross bone changes (on the cutting surface) were depletion of cancellous bone (porosity) and marked reduction in the thickness of the cortical bone. Severe serous atrophy of medullary adipose tissue was also observed. Microscopically, in the evaluated regions (proximal humerus, distal radius, distal femur, proximal tibia and lumbar vertebral bodies), moderate to marked reduction in the number and thickness of bone trabeculae in the epiphyses and metaphyses of long bones and in the vertebral bodies were observed. The clinicopathological features indicated that the osteoporosis observed was probably caused by malnutrition. The bone changes (decrease in the number and thickness of trabeculae of cancellous bone) suggest that both mechanisms, poor bone formation and increased bone resorption, contributed to the occurrence of osteoporosis in the goats of this study.